Mechanical Properties and Morphological Characteristics of Arall Reinforced with Trgo Doped Epoxy Resin [Propiedades Mecánicas y Características Morfológicas de Arall Reforzado Con Trgo Dopando Su Resina Epóxica] - Monsalve-Gonzalez, A; Solis-Vidal, R (Universidade Federal do Rio de Janeiro, 2018)
Mechanical properties in tension, bending, fatigue and lap-shear in two different proportions (0.5%wt and 1%wt) of TRGO (Thermally Reduced Graphite Oxide) doped ARALL (Aramid Aluminium Laminate) were examined. The materials and their failure modes were characterized morphologically by examination through SEM (Scanning Electron Microscopy). Some mechanical properties of ARALL were improved when doped with 0.5% of TRGO, showing a significant increase of fatigue properties, as well as a change in fracture surface morphology. Tension and bending properties showed variable results and further studies should be carried out to arrive to definitive conclusions, while lap-shear testing showed lower shear values. The results were statistically validated through mono-factorial variance analysis. Comparing the present results with previous work on CNT (Carbon Nanotubes) doped ARALL, it can be stated that: (a) TRGO doped ARALL showed improved fatigue properties when compared with non-doped ARALL, but in a less effective way than doping with CNT, (b) TRGO doped ARALL tension properties showed no significant variation as compared with ARALL alone, showing no deleterious influence as in the CNT doping case, (c) TRGO doped ARALL bending properties resulted better than non-doped ARALL, but similar than those obtained when doping with CNT and (d) TRGO decreased the adherence between aramid fiber impregnated L20 epoxy resin and aluminium. These last results are sustained based on observed improvements as a percentage value, without a statistical variance analysis made on CNT doped ARALL. © 2018, Universidade Federal do Rio de Janeiro. All rights reserved.